Comparative growth of some African clovers planted at different times - Akundabweni, L.S.; Lazier, John R.; Lemme, G. (1991)
A study was conducted in the Shoa plateau of the north-western Ethiopian highlands to investigate the patterns of dry matter production, the effect of season of establishment, and the best time of harvest for 8 native African and 3 exotic clovers. The native clovers gave higher dry matter yields than the exotic clovers. Dry matter yields were higher in the March-rains planted crop than the June-rains planted croThe yield of native clovers increased with time for the March-rains crop but not the June-rains croThis could be largely explained by the difference in the number of days of available moisture for the two crops, the earlier planted crop having a longer growing season.